Healthcare middle managers' experiences of developing capacity and capability: a systematic review and meta-synthesis - Trude Anita Hartviksen; Jessica Aspfors; Lisbeth Uhrenfeldt (BMC, 2019)
Abstract Background Healthcare middle managers play a central role in reducing harm, improving patient safety, and strengthening the quality of healthcare. The aim of this systematic review was to identify the present knowledge and critically discuss how healthcare middle managers experienced to develop the capacity and capability for leadership in a healthcare system characterized by high complexity. Methods This comprehensive systematic review provided evidence of healthcare middle managers' experiences in developing the capacity and capability for leadership in public healthcare. The three-step literature search was based on six databases and led by a PICo question. The review had a critical hermeneutic perspective and was based on an a priori published, protocol. The methods were inspired by the Joanna Briggs Institute and techniques from Kvale and Brinkmann. The results were illustrated by effect size, inspired by Sandelowski and Barroso. Results Twenty-three studies from four continents and multiple contexts (hospitals and municipal healthcare) published from January 2005-February 2019 were included. Based on experiences from 482 healthcare middle managers, 2 main themes, each with 2 subthemes, were identified, and from these, a meta-synthesis was developed: Healthcare middle managers develop capacity and capability through personal development processes empowered by context. The main themes included the following: 1. personal development of capacity and capability and 2. a need for contextual support. From a critical hermeneutic perspective, contrasts were revealed between how healthcare middle managers experienced the development of their capacity and capability and what they experienced as their typical work situation. Conclusions This review provides evidence of the need for a changed approach in healthcare in relation to criticisms of present organizational structures and management methods and suggestions for how to strengthen healthcare middle managers' capacity and capability for leadership in a healthcare system characterized by high complexity. Evidence of how leadership development affected the clinical context and, thus, the quality of healthcare was found to be a field requiring further research. PROSPERO registration number CRD42018084670